2008
DOI: 10.1007/s10875-008-9189-0
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous Peptides on the Nontypeable Haemophilus Influenzae P6 Outer Membrane Protein

Abstract: Our present results indicate that these peptides would be candidates for a widely applicable peptide vaccine formulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Ishida et al (40) established P6-specific CD4 ϩ T-cell lines restricted by the human histocompatibility leukocyte antigen (HLA)-DR9 molecule and revealed a human T-cell epitope on P6 and its core peptide sequence (p77 to 85; EYNIALGQR). Nomura et al (41) studied promiscuous peptides on the nontypeable H. influenzae outer membrane protein P6, identified that human B-cell epitope was located on p71 to 85, which could be recognized by T-cell lines (TCL) in the restriction of HLA-DR9, and induced a proliferative response. The epitope peptide sequences on P6 in these two studies were successfully predicted (named P6-95) in the study as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ishida et al (40) established P6-specific CD4 ϩ T-cell lines restricted by the human histocompatibility leukocyte antigen (HLA)-DR9 molecule and revealed a human T-cell epitope on P6 and its core peptide sequence (p77 to 85; EYNIALGQR). Nomura et al (41) studied promiscuous peptides on the nontypeable H. influenzae outer membrane protein P6, identified that human B-cell epitope was located on p71 to 85, which could be recognized by T-cell lines (TCL) in the restriction of HLA-DR9, and induced a proliferative response. The epitope peptide sequences on P6 in these two studies were successfully predicted (named P6-95) in the study as well.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenicity of P6 is facilitated by the presence of a CD4 helper T cell epitope [13], [24], [25]. The presentation of the epitope to P6-specific CD4 + T cells is likely enhanced by the presence of the lipid motif on the antigen when endocytosed by the APC upon recognition by TLR2.…”
Section: Discussionmentioning
confidence: 99%
“…Although it comprises less than 1% of the total outer membrane protein, the minor outer membrane lipoprotein P6 is highly conserved at the nucleotide and amino acid level among all tested strains of NTHI due to its integral function as an anchor between the outer membrane and the bacterial cell wall (20). Importantly, in consideration of vaccine development, P6 expresses epitopes on the outer membrane accessible for antibody binding and contains an immunodominant T cell epitope for assessing generation of cellular immunity (2123). We have previously demonstrated that T cell responses to P6 are associated with relative protection against NTHI infection in adults with COPD (24).…”
Section: Introductionmentioning
confidence: 99%